2015
DOI: 10.1093/cid/civ511
|View full text |Cite
|
Sign up to set email alerts
|

Single-Tablet Emtricitabine-Rilpivirine-Tenofovir as HIV Postexposure Prophylaxis in Men Who Have Sex With Men

Abstract: NCT01715636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
2
19
0
4
Order By: Relevance
“…One of the studies showed that in MSM, a single tablet of FTC‐RPV‐TDF effectively protected the participants from HIV. It was well tolerated with high adherence to the drug by the participants . RPV on macaques infected with SIV containing HIV‐1 reverse transcriptase (RT) helped to decrease plasma viremia, and the effect lasted for about 15 weeks.…”
Section: Non‐nucleoside Reverse Transcriptase Inhibitormentioning
confidence: 99%
“…One of the studies showed that in MSM, a single tablet of FTC‐RPV‐TDF effectively protected the participants from HIV. It was well tolerated with high adherence to the drug by the participants . RPV on macaques infected with SIV containing HIV‐1 reverse transcriptase (RT) helped to decrease plasma viremia, and the effect lasted for about 15 weeks.…”
Section: Non‐nucleoside Reverse Transcriptase Inhibitormentioning
confidence: 99%
“…The nonnucleoside reverse transcriptase inhibitor (NNRTI) rilpivirine (RPV) is FDA approved as a component of combination antiretroviral therapy (ART) that includes TFV disoproxil fumarate and FTC in a once-daily oral pill. RPV in combination with other antiretroviral drugs has been evaluated for efficacy as ART (7)(8)(9) and postexposure prophylaxis (10). RPV also has been developed in a nanoparticle long-acting formulation (RPV LA) to improve adherence (11,12).…”
mentioning
confidence: 99%
“…If started within 72 hours of exposure and taken for 28 days with good adherence, PEP significantly reduces the likelihood of the person becoming HIV‐positive because it can stop HIV from establishing itself in a person's immune cells even after the virus has entered a person's body . Although PEP is not 100% effective, high rates of success have been reported (e.g. 81% among patients using older‐style treatments and up to 100% among patients using newer treatments ).…”
Section: Discussionmentioning
confidence: 99%